ANALISIS MANAJEMEN SUMBER DAYA MANUSIA DI INSTALASI CENTRAL STERILE SUPPLY DEPARTEMENT RUMAH SAKIT X KOTA SEMARANG DALAM MEMENUHI STANDAR KOMPETENSI DAN KEWENANGAN STAF AKREDITASI RUMAH SAKIT - Indrawati, Chaterina Ria Wahyu; Arso, Septo Pawelas; Budiyanti, Rani Tiyas (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
The most influential factor in achieving the quality of hospital services is human resource management. Fulfilling the standards set in hospital accreditation for each service delivery to patients, both medically and non-medically, is an effort that can be made to maintain service quality. The research method used is a qualitative method with a descriptive approach with the aim of getting an overview of the state of human resource management in the CSSD Installation of X Hospital Semarang City. The results of the study found that human resource management at the CSSD Installation staff had met the KKS SNARS standards and so far had been able to support maintaining the maximum results of hospital accreditation. However, in practice, there were things that were not suitable, such as recruitment of staff who did not meet the predetermined requirements, there was a shortage of applicants due to the requirements being set too high. There are also staff whose job descriptions are only oriented to the output of the CSSD installation, namely the procurement of sterile goods for other units in the hospital in a timely manner without regard to applicable standards and procedures such as the use of personal protective equipment. With this research, it can be used as material for consideration for hospitals in conducting in-depth evaluations in the process of implementing human resource management.